Логічні аналізатори. Їх різновиди та можливості використання при розробці та в вимірювальній практиці - Резуненко, К. І.; Воргуль, О. В. (My University, 2021)
For the tracking of foldable signals, it has long been possible to adjust the signals in the clock, frequency areas - oscillography, characterograph, and spectrum. Along with the appearance of microprocessors and multi-bit equipment, it is necessary to receive additional signals. Often this is the problem of solving logical analysts.
Keywords: логічні аналізатори; дані цифрові